INTEGRITY IN THE ASSESSMENT OF MANAGEMENT PERSONNEL OF THE ORGANIZATION - Yunussov M. B.,; Yessirkepova А. M.,; Aliyeva Zh. T., (Academic Journal of Physical and Chemical Sciences, 2020)
The paper considers the complex factors in the assessment of the managerial staff of the organization. The main components of the mechanism for improving the forms and methods of stimulating the work of managerial personnel through the development of an effective methodology for evaluating their work are disclosed. The assessment of the work of management personnel must be approached, first of all, from the perspective of complexity, which means the fact that the factors that have a final impact on work efficiency must be structured in the form of an algorithm that can clearly and efficiently give assessment criteria that are understandable to all respondents. The developed algorithm for evaluating managerial personnel is based on two components: the formation of criteria according to the requirements of the industry specifics and the compliance with these requirements of the manager’s professional qualities. The development of assessment criteria is based on three main areas: personal data, professional skills and needs of the industry.